Mastomys natalensis is a possible natural rodent reservoir for encephalomyocarditis virus. (3rd March 2021) - Kishimoto, Mai; Hang'ombe, Bernard M.; Hall, William W.; Orba, Yasuko; Sawa, Hirofumi; Sasaki, Michihito
Abstract : Encephalomyocarditis virus (EMCV) infects a wide range of hosts and can cause encephalitis, myocarditis, reproductive disorders and diabetes mellitus in selected mammalian species. As for humans, EMCV infection seems to occur by the contact with animals and can cause febrile illnesses in some infected patients. Here we isolated EMCV strain ZM12/14 from a natal multimammate mouse ( Mastomys natalensis: M. natalensis ) in Zambia. Pairwise sequence similarity of the ZM12/14 P1 region consisting of antigenic capsid proteins showed the highest similarity of nucleotide (80.7 %) and amino acid (96.2%) sequence with EMCV serotype 1 (EMCV-1). Phylogenetic analysis revealed that ZM12/14 clustered into EMCV-1 at the P1 and P3 regions but segregated from known EMCV strains at the P2 region, suggesting a unique evolutionary history. Reverse transcription PCR (RT-PCR) screening and neutralizing antibody assays for EMCV were performed using collected tissues and serum from various rodents ( n =179) captured in different areas in Zambia. We detected the EMCV genome in 19 M . natalensis (19/179=10.6 %) and neutralizing antibody for EMCV in 33 M . natalensis (33/179=18.4 %). However, we did not detect either the genome or neutralizing antibody in other rodent species. High neutralizing antibody litres (≧320) were observed in both RT-PCR-negative and -positive animals. Inoculation of ZM12/14 caused asymptomatic persistent infection in BALB/c mice with high antibody titres and high viral loads in some organs, consistent with the above epidemiological results. This study is the first report of the isolation of EMCV in Zambia, suggesting that M. natalensis may play a role as a natural reservoir of infection.